The Party Is Over : The New Louisiana Politics - Maloyed, Christie L.; Cross, Pearson (Book collections on Project MUSE., 2022)
"For decades, the Louisiana political scene has been a source of interest and intrigue for scholars and casual observers alike. In recent years, the state's political, economic, and environmental challenges have drawn sustained attention from regional and national media. Long heralded for its unique politics, observers have typically focused on Louisiana's distinctive political culture, including jungle primaries, colorful candidates, and tolerance for scandal. However, recent shifts have eroded the state's distinct political character, placing it in line with national political trends of partisan realignment, political polarization, and outside influence in state and local elections. Contributors to "The Party is Over" explore these changes, focusing on the shifts that created a new Louisiana politics. The most recent scholarly treatment of Louisiana's political system is Wayne Parent's Unmasking the Carnival (LSU Press). Since its publication in 2004, Louisiana has faced unprecedented environmental disasters-Hurricanes Katrina and Rita, the Deepwater Horizon oil spill, and the 2016 Flood-as well as an array of economic challenges and policy upheavals, including disinvestment in higher education funding, Medicaid expansion, and criminal justice reform. "The Party is Over" investigates these recent shifts in institutions, politics, and policy and situates these trends in the context of national politics. The volume brings together top scholars, journalists, and policy analysts to provide an updated assessment of Louisiana's political situation. It is a valuable introduction to Louisiana's political institutions, political culture, and policy issues that also offers context and new insights for long-time"--